ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STOCK REPURCHASE PADA PERUSAHAAN MANUFAKTUR DI BEI - ADITYA MASTAN, ALOYSIUS (: 2303-1719)
stock exchange which has been owned by the shareholders. Stock repurchase is one to use retained profits of the company. This study aimed to examine the effect of excess capital, price earnings ratio, and leverage to repurchase stock. The research design was quantitative with the hypothesis. Object of study is a manufacturing company listed on the Indonesia Stock Exchange the period 2005-2010. The analysis technique used is multiple linear regression. The type of data used quantitative data in the form of Balance Sheet December 31, 2005 to 2010, income tatement, cash flow statement for the year ended December 31, 2005-2010 and qualitative data in the form of notes to the financial statements of 2005-2010 and the statement of changes in equity. Sources of data obtained from the IDX website. Data analysis techniques using multiple linear regression. The analysis showed that no excess cash flow positive effect on stock repurchase, this is because the company can not generate cash flows that can be distributed to shareholders. Price earnings ratio is not a positive influence on stock repurchase, this is because the company generates profits, causing a small decrease in the value of shares in the future. Leverage positive influence on stock repurchase repurchase because it can be used to distribute excess cash to shareholders and when the company distributes capital will reduce equity and increase the leverage ratio.